The Influence of Work Motivation and Work Environment on the Performance of Employees of the UKM Cooperative Office of Kulon Progo District, Yogyakarta Special Region - Muhammad Isnaini Fathoni; Retno Puji Hartati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Organizational achievement is influenced by the work environment where employees carry out activities also have an important role in improving their performance. The work environment refers to the material and psychological conditions of employees in the organization. This study aims to determine the effect of work motivation and work environment on employee performance at the Kulon Progo Regency Small and Medium Enterprises Cooperative Office. In this study, the data collection techniques used were questionnaires, observation, documentation and literature study. The analysis used is instrument test, classical assumptions, multiple regression, hypothesis testing, and R2 estimation. Sampling by distributing questionnaires directly to 37 samples. The results of data processing from motivation (X1) have a positive and significant effect on employee performance, namely tcount 2.573> ttable 2.032 with a significance of 0.015 <0.05 and the work environment (X2) has a positive and significant effect on employee performance, namely tcount 2.903> ttable 2.036 with a significance of 0.006 <0.05. Fcount value 7.803> Ftable 3.28, with a significance value of 0.002 <0.05. This means that motivation and work environment simultaneously affect employee performance. The results of the coefficient of determination test obtained an R-square value of 0.315 or 31.5%, which means that the influence of the independent variables on the dependent variable and the rest is influenced by other factors outside the research variables.